PENGARUH MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS V SDN JELEKONG - Asep Priatna; Indriani Lestari; Acep Roni Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research is motivated by students in elementary schools who lack critical thinking skills. The purpose of this study is to find out how to influence and improve students' critical thinking skills after using the Problem Based Learning model for fifth grade students at SD Negeri Jelekong, Kp Ninerang, Jelekong Village, Baleendah District, Bandung Regency, Academic Year 2022/2023. Therefore the researcher was interested and took the title